The Performance Gap in Sport Can Help Determine Which Movements Were Most Essential to Human Evolution - Carroll, Collin (Frontiers in Physiology, 2019)
Men outperform women in sports that require muscular strength and endurance, but the magnitude of this performance gap (PG) does not appear to be constant; that is, the PG between men and women is greater in some sports than it is in others. Here, we examine the size of this gap within the realm of track and field by comparing the top 50 world-record performances of men to the top 50 records set by women in a number of long-distance running, medium-distance running, short-distance running, and jumping events. While women do not perform at the level of men in any track and field event, the magnitude of the PG trends up or down depending on the type of event. Jumping events exhibit a larger gap between the sexes than do running events, and short-distance running events show a smaller disparity between the sexes than do medium- or long-distance running events. This difference suggests that general sexual dimorphism does not explain why female performance is relatively closer to male performance at some track and field events than others. We hypothesize that this trend can be explained by the presence of sex-blind musculoskeletal adaptations (SBMA’s), which accumulate over generations to reduce the size of the PG in certain movements. We conclude that the selection trend favoring in humans should be explored further to determine whether the PG in sport can indeed be used to determine movements to which the human body is adapted.